What Is the Significance of Lysosomal-Mediated Resistance to Imatinib - Mlejnek, Petr (Cells, 2023)
The lysosomal sequestration of hydrophobic weak-base anticancer drugs is one proposed mechanism for the reduced availability of these drugs at target sites, resulting in a marked decrease in cytotoxicity and consequent resistance. While this subject is receiving increasing emphasis, it is so far only in laboratory experiments. Imatinib is a targeted anticancer drug used to treat chronic myeloid leukaemia (CML), gastrointestinal stromal tumours (GISTs), and a number of other malignancies. Its physicochemical properties make it a typical hydrophobic weak-base drug that accumulates in the lysosomes of tumour cells. Further laboratory studies suggest that this might significantly reduce its antitumor efficacy. However, a detailed analysis of published laboratory studies shows that lysosomal accumulation cannot be considered a clearly proven mechanism of resistance to imatinib. Second, more than 20 years of clinical experience with imatinib has revealed a number of resistance mechanisms, none of which is related to its accumulation in lysosomes. This review focuses on the analysis of salient evidence and raises a fundamental question about the significance of lysosomal sequestration of weak-base drugs in general as a possible resistance mechanism both in clinical and laboratory settings.
Keywords: chronická myeloidní leukemie; lidé; imatinib mesylát; protinádorové látky; Imatinib Mesylate; Lysosomes; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Antineoplastic Agents; lyzozomy